2011
DOI: 10.1186/1475-2840-10-21
|View full text |Cite
|
Sign up to set email alerts
|

Value of oral glucose tolerance test in the acute phase of myocardial infarction

Abstract: BackgroundAlthough European guidelines advise oral glucose tolerance test (OGTT) in patients with acute myocardial infarction (AMI) before or shortly after hospital discharge, data supporting this recommendation are inconclusive. We aimed to analyze whether disturbances in glucose metabolism diagnosed before hospital discharge in AMI patients represents a latent pre-existing condition or rather temporary finding. Additionally, we planned to investigate the value of pre-selected glycemic control parameters as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…Jiménez-Navarro et al reported that in patients admitted with acute coronary syndromes the correlation between the OGTT performed the day after coronary revascularisation and the OGTT 1 month later was poor (weighted κ 0.23±0.1) [5]. Bronisz et al also showed that the prevalence of disturbances in glucose metabolism as assessed by OGTT at 3 months was significantly lower than at discharge (29% vs. 48%) for patients with acute myocardial infarction (AMI), implying that the dysregulation in glucose metabolism observed in such patients may be transient [6]. On the other hand, Norhammer et al suggested that the rates of abnormal glucose regulation (based on OGTT) in patients with AMI were similar prior to discharge and 3 months after discharge (although the degree of concordance was not reported) [7].…”
Section: Ami Acute Myocardial Infarction Cad Coronary Artery Diseasementioning
confidence: 99%
“…Jiménez-Navarro et al reported that in patients admitted with acute coronary syndromes the correlation between the OGTT performed the day after coronary revascularisation and the OGTT 1 month later was poor (weighted κ 0.23±0.1) [5]. Bronisz et al also showed that the prevalence of disturbances in glucose metabolism as assessed by OGTT at 3 months was significantly lower than at discharge (29% vs. 48%) for patients with acute myocardial infarction (AMI), implying that the dysregulation in glucose metabolism observed in such patients may be transient [6]. On the other hand, Norhammer et al suggested that the rates of abnormal glucose regulation (based on OGTT) in patients with AMI were similar prior to discharge and 3 months after discharge (although the degree of concordance was not reported) [7].…”
Section: Ami Acute Myocardial Infarction Cad Coronary Artery Diseasementioning
confidence: 99%
“…Therefore, it is sound to perform OGTT in the ACS patients to improve search for such an important disease as DM 42 . Bronisz et al 43 reported that a substantial proportion of AMI patients with the abnormal result of OGTT soon after AMI, can have a normal glucose tolerance 3 months after AMI. To the contrary, a meta-analysis found that < 10% of ACS patients diagnosed with DM by means of an OGTT before discharge will have a different result at the follow-up OGTT 42 .…”
Section: Comparison Of the Most Important Tools To Detect Dm In Ami (mentioning
confidence: 99%
“…Nevertheless, early performance of OGTT, the exclusion of high-risk patients with heart failure and renal failure, which were shown to be independent risk factors of death in patients with glucose abnormalities [17], could have had a major impact on the obtained results. In published studies, the clinical characteristics of patients with AMI and newly detected abnormal glucose tolerance are not equivocal, however, those patients are generally more likely to be older, female, hypertensive, overweight or obese, they have a worse left ventricle ejection fraction and renal function, higher glycemia measured on hospital admission, higher fasting glucose levels, higher glycosylated hemoglobin and insulin, proinsulin, and triglycerides than patients with normoglycemia [12, 13,14,15,16,17,18,19,20,21]. In the majority of studies there were no differences in cardiovascular medical history with respect to different glucose abnormalities, except a study by Bartnik et al which showed that patients with abnormal glucose tolerance had a trend towards more heart failure history [21].…”
Section: Value Of Oral Glucose Tolerance Test In Acute Phase Of Acutementioning
confidence: 99%
“…There are several studies in which the oral glucose tolerance test was repeated after the acute phase of myocardial infarction [12, 13,14,19,20,22,23]. One of the first studies was conducted by Norhammar et al who showed that at hospital discharge the prevalence of NGT, IGT or DM was: 34%, 35%, 31%, and 35%, 40%, 25% respectively after 3 months.…”
Section: Value Of Oral Glucose Tolerance Test In Stable Patients Aftementioning
confidence: 99%